Psychological and social consequences among mothers suffering from perinatal loss: perspective from a low income country - Gausia, K.; Moran, A.; Ali, Mohammed; Ryder, D.; Fisher, C.; Koblinsky, M. (BioMed Central Ltd, 2011)
Background. In developed countries, perinatal death is known to cause major emotional and social effects on mothers. However, little is known about these effects in low income countries which bear the brunt of perinatal mortality burden. This paper reports the impact of perinatal death on psychological status and social consequences among mothers in a rural area of Bangladesh. Methods. A total of 476 women including 122 women with perinatal deaths were assessed with the Edinburgh Postnatal Depression Scale (EPDS-B) at 6 weeks and 6 months postpartum, and followed up for negative social consequences at 6 months postpartum. Trained female interviewers carried out structured interviews at women's home.Results. Overall 43% (95% CI: 33.7-51.8%) of women with a perinatal loss at 6 weeks postpartum were depressed compared to 17% (95% CI: 13.7-21.9%) with healthy babies (p = < 0.001). Depression status were significantly associated with women reporting negative life changes such as worse relationships with their husband (adjusted OR = 3.89, 95% CI: 1.37-11.04) and feeling guilty (adjusted OR = 2.61, 95% CI: 1.22-5.63) following the results of their last pregnancy outcome after 6 months of childbirth. Conclusions. This study highlights the greatly increased vulnerability of women with perinatal death to experience negative psychological and social consequences. There is an urgent need to develop appropriate mental health care services for mothers with perinatal deaths in Bangladesh, including interventions to develop positive family support.